Sistem Pencatatan dan Pelaporan Data Tuna Madidihang oleh Nelayan Kecil di Latuhalat, Ureng, Assilulu dan Larike - Daniel Z.K. Wambrauw; Lilis W. Talaut; Lolita Tuhumena; Lalu Panji Imam Agamawan (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2022)
Sustainable of fishery need certainly fish resources of management is to exploited fish resources with considered fish resources of sustainabile. Challenges to kept fish resources of sustainable is quite complex problem that enough complete in fishery development. The aim of this research is evulated the recording system and fishery reported in business level of people’s fisheries. The study was conducted for 6 months from November 2018 -January 2019. Data required in the study consists of primary data and secondary data. Sampling is done purposively of 90 fisherman (30%) from total population of tuna fishermen line which is still active doing fishing activity. Research methods used statistic descriptive of analysis.